Optimal voltage and current selection for turboelectric aircraft propulsion networks - Ibrahim, Kingsley; Sampath, Suresh; Nalianda, Devaiah (IEEE, 2020)
Deploying electrical systems for aircraft propulsion have been identified as a potential solution, for reducing the environmental impact of the increasing air transport usage. However, the implementation of this system needs to be done at a suitable voltage and current combination. The aim of this work is to propose a clear procedure, for deriving a suitable voltage and current for an electrical propulsion system, based on the aircraft dimensions and thrust requirement. The approach presented, considers feasibility and minimum mass as boundary and target respectively. The results show that the fan configuration and thrust requirement directly influence the choice of optimal voltage and current. This is due to the varied impact on device sizes and overall propulsion system performance. Major drivers of the selected voltage and current are the loading coefficient, speed and torque requirement of the fan. The knowledge of these is a requirement to arrive at an optimal voltage for the propulsion system
Keywords: Design; Motor; Torque; Speed